Reluctance to organ donation in Iran's brain-dead families: a case study of Shiraz city - Freshte Nouzari; Seyed Samad Beheshty; Ramin Moradi (Shahid Beheshti University of Medical Sciences, 2024)
Background: In Iran, a large number of people in need of organ transplants die every year and many families are not willing to donate organs. The question is here why do such families refuse to donate deceased brain-dead organ(s)? Method: This study was carried out using grounded theory. The research population was 23 individuals who refused to donate organs and dwelled in Shiraz City which they have selected by snowball sampling. Results: Some reasons behind their decisions: traditionalism, non-cognizance of brain-dead individuals, normative pressure, trust, religious beliefs, patriarchal attitudes, significant others, disbelief in the death of a loved one, hope of recovery, compassion for the one's patient and inability to make decisions  Conclusion: Results showed that cultural and social barriers factors play pivotal roles in not donating deceased brain-dead organs. In this way, medical advances in organ transplantation can only be useful if the factors mentioned are soundly discussed.